2016
DOI: 10.1007/s40145-015-0171-z
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behaviour of C/C–SiC composites—A review

Abstract: Ceramic matrix composites made of carbon fibres and carbon matrix (C/C) are generally used for aircraft structures and brake discs due to their low density, and good thermal, mechanical, and tribological properties. Silicon carbide (SiC) can be introduced to the matrix to improve the performance of C/C composites, because it increases the hardness and thermal stability, and decreases the chemical reactivity, which leads to the improvement of tribological properties of C/C composites. Thus carbon-carbon silicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(26 citation statements)
references
References 59 publications
0
25
0
1
Order By: Relevance
“…It is observed that the value of Weibull modulus, 'm', increases with increasing content of kalsilite in the matrix. 19 This phenomenon can be attributed to the presence of fine kalsilite crystal in the matrix and the absence of microcracks in the samples (Figs 6 and 7). The high values of 'm' (m = 10.07 to 17.06) confirm the reliability of these samples.…”
Section: Resultsmentioning
confidence: 90%
“…It is observed that the value of Weibull modulus, 'm', increases with increasing content of kalsilite in the matrix. 19 This phenomenon can be attributed to the presence of fine kalsilite crystal in the matrix and the absence of microcracks in the samples (Figs 6 and 7). The high values of 'm' (m = 10.07 to 17.06) confirm the reliability of these samples.…”
Section: Resultsmentioning
confidence: 90%
“…Carbon materials, especially carbon/carbon composites are deemed to be the most potential materials in the eld of aerospace and aeronautical owing to their superior high-temperature mechanical properties, for instance, low coe cient of thermal expansion, outstanding thermal shock resistance, high strength at extreme temperature and so on [1][2][3][4]. Unfortunately, the defect that carbon materials easily fail above 500 ℃ due to the oxidation of carbon is unable to be ignored [5], which causes the applications of carbon materials are severely hampered in an oxygen-containing environment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the high cost, low oxidation resistance and unstable friction behaviour of C/C composites limits its applications [6]. In order to overcome these disadvantages of C/C composites, SiC was incorporated in the carbon matrix to enhance its oxidation resistance and tribological performance [7]. Incorporation of SiC increases the hardness and thermal stability, and decreases the chemical reactivity which leads to the improvement of frictional properties of C/C composites.…”
Section: Introductionmentioning
confidence: 99%